Unpacking the Layers: A Comparative Insight into Differentiated Instruction Strategies for Deeper Learning Across Educational Contexts - Ratna Juwita; Fatma Sukmawati; Eka Budhi Santosa; Budi Tri Cahyono; Relly Prihatin; Suparmi Suparmi; Jovita Ridhani; Sari Trisnaningsih (PT. Pusmedia Group Indonesia, 2025)
Indonesian teachers, especially in Central Java, encountered challenges in crafting differentiated activities to create deeper learning form students. They include being able to determine students’ prior knowledge and readiness, along with what works best for how learners like to learn (themselves using delivery and assessment methods) in related to individual learners. The research was conducted to explore kindergarten, elementary and secondary school teachers (n = 112) practices about implementation of differentiated instruction for deeper learning in public and private schools n= 35 using descriptive qualitative method. The data collection technique was carried out with Self-Reported Essays, Video-Taped DI Practices and Interviews at the Teacher Appreciation event in Indonesia. The findings revealed that the most frequently used in all levels are giving explanation, providing additional support, and set goals. Furthermore, important variations in the selection of materials, goal introduction, prior knowledge activation, adapted instruction, grouping, adapted materials and varied assessment were also found across levels. This article suggests that teacher professional development be focused on strengthening differentiated teaching practices through classroom supervision programs and practical workshops. Areas of development that need to be carried out include understanding the concept of DI, the application of techniques such as flexible grouping and formative assessment, the design of differentiated lesson plans, and the use of adaptive learning media and supporting technologies.